Optimal originator valuation and the global financial crisis. (20th February 2012) - Petersen, M.A.; Mukuddem‐Petersen, J.; Thomas, S.; de, B.
SUMMARY In this paper, we discuss subprime mortgage design in both a theoretical‐ and numerical‐quantitative framework. In particular, we model mortgages that are able to fully amortize, voluntarily prepay (involving prepayment and possibly refinancing), or default. In this regard, we find that mortgage refinancing is curtailed by high loan‐to‐value ratios because of house price depreciation, whereas low loan‐to‐value ratios increase mortgagor house equity. Furthermore, an optimal originator valuation problem under mortgage origination is solved. In this case, optimal mortgage value and rates as well as profit are computed. The paper supports the view that the subprime mortgage crisis was partially caused by the intricacy of design of subprime mortgages that led to information (asymmetry, contagion, inefficiency, and loss) problems, valuation opaqueness, and ineffective risk mitigation. Copyright © 2012 John Wiley & Sons, Ltd.